Contextual Effect of Village on the Incidence of Tuberculosis in Children in Surakarta, Central Java: A Multilevel Analysis Evidence - Dyah Ayu Saputri; Yulia Lanti Retno Dewi; Bhisma Murti (Journal of Epidemiology and Public Health, 2019)
Background: Indonesia is in the second place with the highest burden of tuberculosis (TB) in the world. Childhood is a period of rapid growth that requires efforts to maintain children's health. At the time the child still has a low immune system making it vulnerable to a disease including TB. The problem of TB in children requires better attention in child TB control programs. This study aimed to analyze the contextual influence of villages on the incidence of TB in children.Subjects and Method: This was a case-control study conducted in 25 villages in Surakarta, Central Java, from August to September 2019. A sample of 200 children aged 0 to 18 years was selected by fixed disease sampling. The dependent variable was the incidence of TB in children. The in